Staying local in a global discourse: A study of comments on selected minifictions by a Sundanese woman writer in Fiksimini Basa Sunda Facebook Group - Raden Safrina (Indonesian Journal of Applied Linguistics, 2022)
This paper examines the social meanings from interactions of a Facebook group which posts mini fictions in the Sundanese language. The examination was more specifically focused on comments for mini fiction posts written by a woman writer. Following the idea of locality as essentially ‘a situatedness’ (Ahmed, 2000), the study framed the interactions as locality and situated the locality as it intertwines and intersects with more global issues. The study began by selecting mini-fictions in the Sundanese language that received at least 100 comments from their readers. Interactions arising from comments about the selected texts were examined to situate the intertwine of locality in the texts and the more global responses in the comment sections. Selected interactions were then examined using a Hallidayan critical discourse analysis. Taking situatedness as the focus, the analysis indicates that interpersonal themes attracted comments where locality and globality are situated to construct irony where locality pales in the face of globality. Therefore, it seems that more efforts should be made to strategically situate locality in a more vantage point in the global world.